A new custom-made bivalve brace for pectus carinatum in children and adolescents: preliminary promising experience of 140 patients from a tertiary center - Frediani, Simone; Zarfati, Angelo; Pardi, Valerio; Aloi, Ivan; Bertocchini, Arianna; Accinni, Antonella; Beati, Federico; Pasanisi, Massimiliano; Inserra, Alessandro (Frontiers in Pediatrics, 2024)
Introduction International research suggests that poor patient compliance is the main cause of tutor failures in the context of potential novel orthopedic bivalve braces for conservative treatment of pectus carinatum. Our entire experimental study is based on the hypothesis that a rigid bivalve brace that patients can accept could solve the main problem associated with the conservative approach—poor compliance. The hypothesis was to reduce the thickness and weight of the classic bivalve brace to ensure concealment and make it sustainable enough to be worn several hours a day without compromising its therapeutic efficacy. Materials and method The research was conducted from January 2020 to December 2022 to ensure follow-up of all participants for at least 6 months. In 36 months, 140 patients with pectus carinatum were assessed and conservatively treated with the studied guardian to analyze the therapeutic efficacy of the bivalve brace and patient compliance. From the initial visit, the parents and patient were informed that this is a 2-year therapeutic course during which the bivalve brace should be worn at least 23 h a day (with 1 h of abstinence per day for routine personal hygiene practices). Compliance is the key to therapy success, and the duration of treatment depends on patient adherence. Results The exceptional effectiveness of the experimental brace was confirmed by both the questionnaire from the patients (with an average satisfaction rate of 8.9/10) and an assessment of the therapy's results by a properly selected medical committee (with a VAS scale satisfaction of 7.2/10 for symmetric forms and 7.1/10 for asymmetric ones). Conclusion In conclusion, the analyzed data confirmed the research hypotheses. First, none of the 140 patients had cardiovascular diseases directly related to their condition, confirming that pectus carinatum is a pathology of a purely aesthetic nature. Second, a cheap, lightweight, and easily obscured brace significantly improved patient compliance. Along with this, the social relevance of the aesthetic aspect today may be an important factor in motivating the study cohort to adhere to therapy. In the past, esthetics and appearance were less relevant at the social level, which may have contributed to the high abandonment and reduced compliance rates of the many studies in the literature.